Penurunan Kecemasan terhadap Masa Depan Ditinjau dari Intensitas Membaca Al-Qur’an pada Dewasa Awal di Yogyakarta - Dela Faridatun Nafisah; Zahro Varisna Rohmadani (EduInovasi: Journal of Basic Educational Studies, 2025)
This research delves into the interplay between how frequently young adults in Yogyakarta engage with the Qur’an and their levels of anxiety about what the future holds. Early adulthood is often marked by uncertainty and stress, stemming from both personal struggles and external pressures such as societal expectations and shifting relationships. To investigate this dynamic, the study employed a quantitative, correlational approach, drawing data from 96 randomly selected participants within the target age group. Data collection relied on a validated and reliable Likert-scale questionnaire to ensure robust measurement. The core findings reveal a notable association: individuals who read the Qur’an more regularly tend to report lower levels of future-oriented anxiety. This suggests that the act of reading the Qur’an may serve as a practical tool for managing worries about the future, offering psychological benefits beyond its spiritual significance for young adults navigating life in Yogyakarta.